Influence of abiraterone acetate on circulating neuromediators in chemotherapy-naïve castration-resistant prostate cancer - Hardenberg, Jost von; Schwartz, Maike; Weiß, Christel (The prostate, 2016)
Background: Abiraterone Acetate (AA) represents a highly effective androgen-receptor (AR) axis targeted agent. Treatment with AA in castration-resistant prostate cancer (CRPC) may partly mediate neuroendocrine differentiation (NED) as an escape mechanism, which may have implications for the choice of sequential therapy in CRPC. We evaluated how treatment with AA influences circulating neuromediators chromogranin A (CGA), neuron-specific enolase (NSE), and pro-gastrin-releasing peptide (Pro-GRP) in chemotherapy-naïve CRPC patients. Methods: We conducted an analysis in chemotherapy-naïve CRPC patients with clinical or radiographic progression of disease. A total of 35 patients were included at five institutions between February 2013 and December 2014. Sixteen of them had received AA. Serum samples were obtained before a docetaxel-based chemotherapy and analyzed in a reference laboratory. Univariable and multivariable analyses were performed to test the influence of AA treatment, its duration of treatment, and other clinicopathological variables on circulating neuromediators. Results: CGA and NSE levels were above the upper limit of normal (ULN) in n = 20 (57.1%) and n = 13 (37.1%), respectively. Treatment with AA and duration of treatment were not associated with levels above the ULN (CGA and NSE) or higher levels (Pro-GRP) of neuromediators. CGA levels were associated with age (P = 0.092), lymph node metastasis (P = 0.014), duration of androgen deprivation therapy (ADT; P = 0.083), and intake of proton pump inhibitors (P = 0.069). Pro-GRP levels were significantly associated with PSA levels (P = 0.002). On multivariate analysis, CGA levels above the ULN were significantly correlated with ADT (P = 0.01) and intake of proton pump inhibitors (P = 0.03). Conclusions: Circulating neuromediators in chemotherapy-naïve CRPC patients were elevated in a high percentage of patients. ADT was found to be a relevant NED driver in this cohort. Our results may imply that patients with CRPC after first-line treatment with AA in CRPC are not at a higher risk for developing NED. The major limitation of the study represents the one-time analysis of neuromediators. Larger studies with serial blood measurements or biopsy analysis before and after treatment are needed to confirm our results.
Gesehen am 20.05.2019